Perancangan Antena MIMO Rectangular Patch Double Layer pada Frekuensi 2,35 GHz - Utami, Eva Yovita Dwi; Gupita, Muhamad Asra; Wahyu, Yuyu (Jurnal Telematika, 2024)
A MIMO microstrip antenna 2x2 with a double layer at a working frequency of 2.35 GHz is designed and realized in this study. The structure of the proposed MIMO antenna consists of two symmetrical rectangular patches made of copper and a substrate made of FR4 Epoxy, which has a relative permittivity of 4.3 and a thickness of 1.6 mm. The proposed 2x2 MIMO antenna is designed with two layers, one main layer and one parasitic layer above the main layer, with a particular air gap. The single-layer and double-layer antenna designs are simulated with software. The simulation results show that the gain of the single-layer antenna is 2.8 dB, while the double-layer antenna reaches 4.55 dB. The bandwidth obtained on the single-layer antenna is 69.8 MHz, and on the double-layer is 102.64 MHz. Thus, there is an increase in gain of 62.5% and an increase in bandwidth reaching 47% on the double-layer antenna. The designed and simulated antenna has been successfully fabricated at a frequency of 2.35 GHz. The measurement results of the fabricated antenna show an increase in gain of 12.5% and an increase in bandwidth of 18.84%.